Designing Sustainable Urban Futures : Concepts and Practices from Different Countries - Marius Albiez
Many 21st century cities have the potential to be sustainable and resource-saving living spaces when multifunctional structures, well-integrated transportation infrastructure, and democratic governance processes are present. Sustainable urban futures require a focus on the needs of humans and environmental best practices, as well as on the creative scope for community-driven sustainability innovations. This book is based on contributions from science and practice to the international symposium on "Sustainable Urban Development at Different Scales" organized by the Institute for Technology Assessment and Systems Analysis at the Karlsruhe Institute of Technology, Karlsruhe, Germany, in May 2014. The symposium used the global urbanization and reurbanization trend as an opportunity to examine cities as sustainable living spaces. This book identifi es concepts, analytic approaches, and practical applications for the design of sustainable urban futures among multiple disciplines and cultural backgrounds.